Analisis Yuridis Penegakan Hukum Terhadap Tindak Pidana Pornografi Dengan Cara Memposting Video Porno Diakun Media Sosial Twitter Diwilayah Hukum Polda Riau - Akel Fernando; Rusdi Rusdi (Journal of Legal Sustainability, 2026)
The purpose of this research is to determine how the law is enforced against perpetrators of the crime of distributing pornography on social media Twitter and to determine the obstacles and constraints in enforcing the law against the distribution of pornographic content on social media Twitter. The research method is an absolute element that must be present in research and the development of science. To obtain maximum and good research results, accuracy, precision, and persistent effort are required. In line with the research topic that focuses on a legal review, in collecting and processing data and materials the author of pornography Ministry of Communication and Information. Based on the results of the study, that the role of the police, especially the Riau Regional Police, in efforts to eradicate the crime of pornography is not solely a matter of law and law enforcement, but also social, cultural, and economic issues that are closely related to the issue of national resilience, so that policies and measures for prevention and eradication are also aimed at maintaining a balance in the obligation to protect state sovereignty, the human rights of victims and witnesses, and the human rights of suspects and defendants.